LEGAL ANALYSIS OF THE USE OF BUYBACK GUARANTEES TO SUPPORT DEVELOPER BUSINESS CAPITALIZATION AND MARKETING - Juli Purwanti; Henry Aspan; Fitri Rafianti (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Developer capital and marketing of their houses greatly affect the Indonesian economy, many developers need capital injections from banks, in addition to capital injections, developers can also obtain convenience in marketing completed houses through mortgages from banks that provide working capital loans. To facilitate mortgage approval for consumers, developers include a repurchase clause or better known as a Buyback Guarantee, a Buyback guarantee is a repurchase guarantee contained in a working capital cooperation agreement between banks and developers born from the principle of freedom of contract and the principle of Prudent in banking. This study aims to find out and explore how this credit agreement can be implemented and how this Buyback Guarantee clause is included in a banking credit agreement so that it can support capital and marketing of the developer's business. This study uses a Descriptive Juridical-Normative approach method. The formulation of the problem in this paper is How are the regulations and legality of the Buy Back Guarantee agreement clause as a form of repurchase guarantee between banks and developers and How the Buyback Guarantee Clause can support the Capital and Sales of the Developer's business. The results of this study demonstrate that the legality of credit agreements incorporating a buyback guarantee clause between banks and developers is based on the principles of freedom of contract and prudential banking principles.